Perancangan Instrumen Penilaian Alternatif Kemampuan Literasi Sains Mahasiswa Biologi Berdasarkan Scientific Literacy Assessment - afrahamiryano afrahamiryano (Eduscience Development Journal, 2022)
Scientific literacy aims to prepare graduates who are sensitive to problems in the surrounding environment and are responsible. To find out that the graduates to be produced have good scientific literacy, it is necessary to design an assessment instrument to measure these abilities. This assessment instrument uses design instructional research to create a design instrument for assessing students' scientific literacy skills. This assessment instrument was developed based on the Scientific Literacy Assessment (SLA).